H2 and H∞ Control with sector bound optimization for Continuous Time Markov Jump Lur'e Systems. (September 2022) - da Silva, L.P.M.; Gonçalves, A.P.C.
Abstract: This paper addresses the H 2 and H ∞ control of Markov Jump Systems subject to a class of nonlinearities that include them on the Lur'e system framework, with sector slope optimization. The proposed controllers are robust to nonlinearities belonging to a sector. We propose mode-dependent controllers; in other words, the Markov mode θ ( t ) is available to controllers. The design of such controllers considers the optimization of the H 2 and H ∞ costs as well as the sector slope, which determines the class of accepted nonlinearities. The results are illustrated through two practical examples: coupled electrical machines and the semi-active suspension of a quarter car.